Desenvolvimento e Automatização do Primeiro Envio numa Cadeia de Abastecimento - Miguel Verdelho Valdrez Teixeira da Silva (2017)
This study was conducted during a Master Thesis in a company environment and it aims to enlighten and describe the work developed at SONAE SR. Competition, economic crisis and all the current market situation force companies to becoming better everyday. In a Retail Industry being better many times means reducing costs without losing quality or, in certain cases, even improving the clients experience. This way, this project seeks to develop and automate a very recent process in the company about First Expedition of products from the Warehouse to the stores. More specifically, the company intends to have developed and coordinated with the Warehouse, the flux of the process being automated to simplify as much as possible the Operator's task. Stock Management in a Sports Fashion Industry is a very reactive activity, making the developments of the project, as well as the process itself, very suitable to changes during time. There are several teams involved and their coordination is essential to the project's success. During the Report, it will be explained how the previous process was, when I arrived the company in February 2017, and all changes and improvements will be justified. The company follows the process and utilizes the tools developed everyday, so it was compulsory to formalize everything. Flowcharts, OPL and even detailed Guides were meticulously done followed by several hours of training given to the all team of the Downstram Suplly Chain of Sport Zone. The Automation previously referred, consummated through Macros programming in Excel VBA, was the major responsible for the reduction of direct costs. Reducing execution time of the process PED in 92%.